Pengaruh Mekanisme Corporate Governance Terhadap Kinerja Keuangan Badan Usaha - Filia Puspitasari; Endang Ernawati (Universitas Airlangga, 2010)
Nowdays, most researches in corporate governance field are conducted by researchers based on rising of many firms to become public corporation. According to this situation, they have to separate their functions on ownership and control of the firm. As result, it will arise agency conflict between owners and managers. The corporation enable solve the problem by apply the corporate governance mechanism optimally. This research is a replication research is conducted by Sanda et al (2005). It’s explained the specific study about the impact of corporate governance mechanism include managerial ownership, board size, outside directors, ownership concentration, and debt toward financial performance that measured by ROA, ROE, PER, and TOBINS’Q. The samples of this research are all corporations which listed at Bursa Efek Indonesia (BEI) by all sectors that delivered financial statement on time by regulation. The period of time in this research determined on 2005-2007. The model is extended by quadratic of managerial ownership, quadratic of board size, quadratic of ownership concentration, CEO foreign and firm size as control variables, and sectoral dummy. The result of this research explained that corporate governance mechanism simultaneously influence to ROA and ROE significantly. On partially, ROA is influenced by CEO foreign, debt, and firm size significantly. And ROE is inluenced by CEO foreign, firm size, and sector of basic industry significantly.